Level of Core Competencies Among UM-CHE Graduating Students: An Asean Integration Workplace Context - Escamis, Jeff E.; Woodell, Bob Keithley S.; Jimenez, Florence Kristina M. (Archives of Business Research, 2025)
The main purpose of the study was to gauge the level of core competencies among UM-CHE graduating students to an ASEAN Integration workplace context. Specifically, this study aims to assess the respondents from the variables extracted from an established ASEAN manual namely: ‘effective communication’, ‘working relationship’ and ‘teamwork’. The study made is a quantitative research. Relevant data was acquired through the use of modified survey questionnaire from an ASEAN manual. The respondents of the study are the graduating students of both HRM and TM programs of the College. There are one hundred (100) respondents for this study, fifty (50) HRM students and fifty (50) TM students. Majority of the respondents are female and mostly are in between the ages of 18 to 21 years old. Among the three (3) indicators, the highest result was ‘teamwork’ with the mean score of 4.37. This explains that the respondents are competent when it comes to working in a team setting. While there is no significant difference in the core competency among UM CHE graduating students when analyzed according to their age and program, results show that sex has a moderating effect to the aforementioned variables of the male and female respondents. The researchers conclude that the level of core competency among UM-CHE graduating students is high and ready for a workplace environment such as of the ASEAN.